A systematic review of adherence to diabetes self‐care behaviours: Evidence from low‐ and middle‐income countries. (10th September 2019) - Mogre, Victor; Johnson, Natalie A.; Tzelepis, Flora; Shaw, Jonathan E.; Paul, Christine
Abstract: Aims: To determine diabetes patient's adherence to five self‐care behaviours (diet, exercise; medication, self‐monitoring of blood glucose [SMBG] and foot care) in low‐ and middle‐income countries. Design: Systematic review. Data sources: We searched MEDLINE, CINAHL, PUBMED, SCOPUS, PsycINFO, EMBASE, Cochrane library and EMCARE for the period January 1990 – June 2017. Review Methods: Title, abstract and full text screening were done according to eligibility criteria. A narrative synthesis of the literature was conducted. Results: A total of 7, 109 studies were identified of which 27 met the review eligibility criteria and were included. All the studies used self‐report of adherence to diabetes self‐care. Studies reported adherence rates in two major forms: (a) mean number of days participants performed a recommended dietary behaviour/activity during the past week; and (b) proportions of participants adhering to a recommended self‐care behaviour. Mean number of days per week participants adhered to a self‐care behaviour ranged from 2.34.6 days per week for diet, 5.5–6.8 days per week for medication, 1.8–5.7 days per week for exercise, 0.2–2.2 days per week for SMBG and 2.2–4.3 days per week for foot care. Adherence rates ranged from 29.9%–91.7% for diet, 26.0%–97.0% for medication taking, 26.7%–69.0% for exercise, 13.0%–79.9% for self‐monitoring of blood glucose and 17.0%–77.4% for foot care. Conclusion: Although most diabetes patients do not adhere to recommended self‐care behaviours, adherence rates vary widely and were found to be high in some instances. Impact: Health services in low‐ and middle‐income countries should monitor adherence to diabetes self‐care behaviours rather than assume adherence and resources should be invested in improving adherence to the self‐care behaviours. Large‐scale accurate monitoring of adherence to diabetes self‐care behaviour is needed and consideration should be given to choice of measurement tool for such exercise. Abstract : 目的: 在于确定中低收入国家的糖尿病患者是否坚持五种自我护理行为(节食、锻炼;药物治疗、 自我血糖监测(简称为"SMBG")和足部护理)。 设计: 系统综述。 资料来源: 我们在1990年1月至2017年6月期间搜索了MEDLINE、CINAHL、PUBMED、SCOPUS、PsycINFO、EMBASE、Cochrane Library和EMCARE。 综述方法: 根据合格标准来筛选标题、摘要和全文。对文献进行了叙述性综合。 结果: 共确定了7109项研究, 其中27项研究符合综述合格标准并得以纳入。所有研究都使用了坚持糖尿病自我护理的自我报告。研究报告了两种主要形式的坚持率:(a) 研究对象在过去一周内采取推荐节食行为/活动的平均天数;(b) 坚持自我护理推荐行为的研究对象比例。每周坚持自我护理行为的平均天数从每周节食2.3‐4.6天、每周服药5.5‐6.8天、每周锻炼1.8‐5.7天、每周自我血糖监测0.2‐2.2天和每周足部护理2.2‐4.3天不等。坚持率从饮食29.9%‐91.7%, 服药26.0%‐97.0%, 锻炼26.7%‐69.0%, 自我血糖监测13.0%‐79.9%和足部护理17.0%‐77.4%不等。 结论: 虽然大多数糖尿病患者不坚持推荐的自我护理行为, 但是坚持率的差异还是很大, 甚至在某些情况下还很高。 影响: 中低收入国家的卫生服务部门应监控糖尿病自我护理行为的坚持情况, 而不是假设在坚持中, 并应投入众多资源来提高对自我护理行为的坚持情况。需要对糖尿病自我护理行为的坚持情况进行大规模精确监测, 并且应考虑为此类锻炼所选的评估工具。